2001
DOI: 10.1029/2001gl013791
|View full text |Cite
|
Sign up to set email alerts
|

The existence of a tertiary ozone maximum in the high‐latitude middle mesosphere

Abstract: Abstract. Modeling and observations provide evidence of the existence of a tertiary ozone maximum in the middle mesosphere restricted to winter high-latitudes. This local maximum occurs at approximately 72 km altitude, at latitudes just equatorward of the polar night terminator. Model analysis indicates that this maximum is the result of a decrease in atomic oxygen losses by catalytic cycles involving the odd-hydrogen species OH and HO2. In the middle mesosphere, at high latitudes, the atmosphere becomes optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 9 publications
7
89
0
Order By: Relevance
“…In a similar way it is possible to explain the existence of the so-called "third ozone maximum" (Marsh et al, 2001;Degenstein et al, 2005) in the mesospheric winter hemisphere at high latitudes and at about 72 km of altitude. In fact, during the night state, the reduced production of HO x components (see Introduction) facilitates the increase in the ozone concentration, but during the "day" such an increase is prevented.…”
Section: The Ozonementioning
confidence: 90%
“…In a similar way it is possible to explain the existence of the so-called "third ozone maximum" (Marsh et al, 2001;Degenstein et al, 2005) in the mesospheric winter hemisphere at high latitudes and at about 72 km of altitude. In fact, during the night state, the reduced production of HO x components (see Introduction) facilitates the increase in the ozone concentration, but during the "day" such an increase is prevented.…”
Section: The Ozonementioning
confidence: 90%
“…This is the tertiary ozone maximum just equatorward of the polar night terminator as described by Marsh et al (2001). 71 individual ozone profiles, which cover a range of atmospheric conditions, namely the Arctic pre-vortex, northern fall and southern spring mid-latitudes, the tropics and the final stage of the Antarctic vortex, were derived from orbit 8597.…”
Section: Microwindowmentioning
confidence: 99%
“…Sonnemann et al, 2007;Hartogh et al, 2004) also known as the tertiary ozone maximum (e.g. Sofieva et al, 2009;Degenstein et al, 2005;Marsh et al, 2001). Sonnemann et al (2007) reported that the MMM is a phenomenon that occurs at high latitudes close to the polar night terminator at around 72 km altitude during nighttime in winter and extends into middle latitudes with decreasing amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…Sonnemann et al (2007) reported that the MMM is a phenomenon that occurs at high latitudes close to the polar night terminator at around 72 km altitude during nighttime in winter and extends into middle latitudes with decreasing amplitude. Marsh et al (2001) interpreted the tertiary peak by considering that in the middle mesosphere during winter, with a solar zenith angle close to 90 • , the atmosphere becomes optically thick to UV radiation at wavelengths below 185 nm, and, since photolysis of water vapour (Reaction R1) is the primary source of odd hydrogen, reduced UV radiation results in less odd hydrogen. The lack of odd hydrogen needed for the catalytic depletion of odd oxygen (Reactions R2, R3, and R4), in conjunction with an unchanged rate of odd-oxygen production (Reaction R5), leads to an increase in odd oxygen.…”
Section: Introductionmentioning
confidence: 99%